Automated sourcing agent (I) - Nguyen Thi Kim Ngan (Nanyang Technological University, 2020)
In recent years, many companies have been putting digital transformation under scrutiny in the effort to be competitive and grow further. A company A that wishes to implement this transformation in their organisation, has approached NTU for help to digitalise their current workflows in strategic purchasing. This project aims to promote an automated sourcing agent to our customer. The agent, empowered by Automation techniques, is a prototype for a web application which serves as a centralised platform for current manually time-consuming tasks. It helps to standardise and optimise those tasks. Thus, it will save our customer many hours of work and allow them to have more time to focus on critical thinking tasks. With this project as a part of the digital transformation initiative, more techniques and solutions can be explored and developed further to be finally implemented in the A’s organisation.